Ventromedial Prefrontal Cortex and Ventral Striatum Volumes in Patients with Alcohol Use Disorder - Tabara, Muhammed Fatih; Koc, Mustafa; Gurok, Mehmet Gurkan; Baykara, Sema; Korkmaz, Sevda; Mermi, Osman; Atmaca, Murad (Routledge Journals, Taylor & Francis Ltd, 2024)
The ventromedial prefrontal cortex (vmPFC) and the ventral striatum are brain regions that are critical for the reward circuit and the maintenance of pleasure. The relationship between these regions and alcohol use disorder has been investigated in the literature in a variety of ways. In this context, it is aimed to determine whether there are structural changes in the vmPFC and ventral striatum regions in patients with alcohol use disorder (AUD) compared to healthy control subjects. Fifteen patients with AUD according to the Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM 5) diagnostic criteria and seventeen healthy controls participated in our study. The volumes of the vmPFC and ventral striatum were measured in subjects. The mean volumes of both sides of the vmPFC were significantly smaller in patients with AUD than those in the healthy control group whereas both sides of ventral striatum volumes were larger. This study is one of the few to examine structural changes in the vmPFC and ventral striatum together in patients with ACD. Although the contribution of the positive findings to the literature is important, more comprehensive studies are needed to strengthen the existing findings.
Keywords: Ventromedial prefrontal cortex; vmPFC; ventral striatum; alcohol use disorder